Dynamics of Research in Public Audit A Bibliometric Evaluation - Wildan Izzulhaq; Widya Ningsih; Payamta; Wahyu Widarjo (Riset Akuntansi dan Keuangan Indonesia, 2024)
The Wirecard AG case in Germany emerges as a highly relevant and in-depth example for exploration within the context of public audit. By evaluating the work that has been done, this study identifies gaps in the existing literature and provides recommendations for research areas that need further deepening. This research uses the Scopus database with 31 articles and uses the VOSviewer application to analyze them. The integration of technology, especially blockchain, into auditing practices is a focal point, enhancing efficiency and security, with the overall research landscape characterized by robust international collaboration and innovation.